Wokeness as a Factor Shaping Teachers’ Conceptions Learners with Special Needs (LSN) vis-à-vis Inclusive Education - Ginalyn Z Andagao; Margie T Lacar; Maribel T Cuadra; Joseph P Casibual Jr (Acitya Wisesa: Journal of Multidisciplinary Research, 2026)
This study explored how social media wokeness shaped teachers’ conceptions of learners with disability within the context of inclusive education. Specifically, it examined (1) teachers’ conceptualizations of wokeness in relation to their professional identity, (2) their role in upholding inclusive values in digital spaces, and (3) the strategies they employed to maintain professional ethics when engaging online. A qualitative exploratory design was utilized, involving ten elementary teachers from the Diplahan District. Data were collected through semi-structured interviews complemented by pakikipagkwentuhan to encourage open and culturally grounded dialogue. Thematic analysis guided the data analysis process. Findings revealed that teachers understood wokeness as heightened awareness and advocacy for inclusion, closely linked to their professional identity and ethical responsibility. Participants recognized their duty to model respectful digital behavior, promote critical digital citizenship, and safeguard learners’ online well-being. They also demonstrated concrete strategies such as practicing responsible communication, verifying information, and maintaining professional boundaries and confidentiality. The study concludes that teachers critically navigate social media and integrate its influence into their commitment to inclusive education. It recommends sustained reflective digital engagement among teachers and continued research on how digital discourse influences inclusive practices in Philippine educational settings.